Influence of Different Extraction Methods on the Changes in Bioactive Compound Composition and Antioxidant Properties of Solid-State Fermented Coffee Husk Extracts - Rossaporn Jiamjariyatam; Pakkapong Phucharoenrak; Siritron Samosorn; Kulvadee Dolsophon; Wanlapa Lorliam; Sukhumaporn Krajangsang; Prapakorn Tantayotai (The Scientific World Journal)
In brewing coffee, a huge amount of food waste is generated; that waste, coffee husks in particular, should be comprehensively exploited. They offer a rich source of bioactive compounds such as caffeine, chlorogenic acid, and trigonelline. The aim of this study was to investigate the effects of extraction methods on the bioactive compounds and antioxidant activity of such waste. Coffee husks in this study were fermented with S. cerevisiae based on a solid-state fermentation technique. The study method included ethanolic or water extraction with varied controllable factors, i.e., temperature (60, 100°C) and extraction technique. Bioactive contents were investigated with the Folin–Ciocalteu assay and 1H-NMR spectroscopy. The antioxidant activity was investigated with DPPH and FRAP assays. Results show that yields were the highest in the extract of fermented coffee husks at 100°C. The highest levels of bioactive contents (total trigonelline content at 3.59% and antioxidant activity at 23.35% (DPPH) and 25.9% (FRAP)) were found in the ethanolic extract of fermented coffee husks at 60°C. The bioactive content and bioactivity, including antioxidant activity, depended on different raw materials, preparation methods, and extraction conditions. This study illustrates the potential for using food waste such as coffee husks as a sustainable source of bioactive compounds or bioactive extracts.